Comparative Genomics of Pseudomonas aeruginosa Strains Isolated from Different Ecological Niches - Jessica Gómez-Martínez; Rosa del Carmen Rocha-Gracia; Elena Bello-López; Miguel Angel Cevallos; Miguel Castañeda-Lucio; Yolanda Sáenz; Guadalupe Jiménez-Flores; Gerardo Cortés-Cortés; Alma López-García; Patricia Lozano-Zarain (Antibiotics, 2023)
The Pseudomonas aeruginosa genome can change to adapt to different ecological niches. We compared four genomes from a Mexican hospital and 59 genomes from GenBank from different niches, such as urine, sputum, and environmental. The ST analysis showed that high-risk STs (ST235, ST773, and ST27) were present in the genomes of the three niches from GenBank, and the STs of Mexican genomes (ST167, ST2731, and ST549) differed from the GenBank genomes. Phylogenetic analysis showed that the genomes were clustering according to their ST and not their niche. When analyzing the genomic content, we observed that environmental genomes had genes involved in adapting to the environment not found in the clinics and that their mechanisms of resistance were mutations in antibiotic resistance-related genes. In contrast, clinical genomes from GenBank had resistance genes, in mobile/mobilizable genetic elements in the chromosome, except for the Mexican genomes that carried them mostly in plasmids. This was related to the presence of CRISPR-Cas and anti-CRISPR; however, Mexican strains only had plasmids and CRISPR-Cas. blaOXA-488 (a variant of blaOXA50) with higher activity against carbapenems was more prevalent in sputum genomes. The virulome analysis showed that exoS was most prevalent in the genomes of urinary samples and exoU and pldA in sputum samples. This study provides evidence regarding the genetic variability among P. aeruginosa isolated from different niches.